The Relationship Between Training Programs and The Achievement Level of Taekwondo Athletes at Dojang Sartika Pati - Salsabilla Pramono Putri; Roas Irsyada (Journal of Physical Education Health and Sport, 2025)
Various factors, including the components of the training program, influence Taekwondo athletes' performance. This study aims to analyze the relationships among training intensity, rest patterns, nutrition, and psychological factors, and the performance of taekwondo athletes at Dojang Sartika Pati. The study used a quantitative correlational design. The research subjects were 30 athletes selected using a total sampling technique. The research instrument was a Likert scale questionnaire developed based on training program indicators and athlete performance. Data analysis was carried out using descriptive statistics, normality and linearity tests, and Pearson correlation tests in SPSS version 25. The results showed that training intensity (r = 0.435; p < 0.05), rest patterns (r = 0.489; p < 0.05), nutrition (r = 0.566; p < 0.05), and factors (r = 0.487; p < 0.05) were significantly related to athlete performance. The nutrition variable showed the strongest relationship to athlete performance. These findings indicate that a comprehensively designed training program that addresses physical, recovery, nutritional, and psychological aspects plays a crucial role in improving taekwondo athletes' performance. Therefore, optimizing all components of the training program needs to be a primary focus in athlete training at the regional level.